Commonalities and differences in healthcare workers’ perceptions of mental burden in Brazil, Colombia, and Germany during the COVID-19 pandemic: a qualitative cross-country study - da Silva, Andrea Tenorio Correia; Sisenop, Felix; Henao, Alexandra Restrepo; Souza, Miriam Regina; Atti, Beatriz; Ruiz, Maria Paula; Marchi, Evaldo; Lindert, Jutta (Frontiers in Public Health, 2025)
ObjectiveTo assess healthcare workers’ (HCWs) perceptions of commonalities and differences in stressors affecting their mental health during the COVID-19 pandemic in Brazil, Colombia, and Germany.MethodWe conducted a qualitative cross-country study between April and September 2022. HCWs from primary and secondary care centers and hospitals participated. The focus groups were recorded, transcribed verbatim, and analyzed using content analysis.Results63 HCWs participated in the study. Factors affecting HCWs’ mental health were categorized into three levels: healthcare system, facility, and individual. Common stressors across all three countries included: a rapid increase in patients and disease severity at the healthcare system level; frequent updates to COVID-19 protocols, staff shortages, and service unpreparedness at the facility-level; and dealing with a new virus and workplace violence at the individual-level. In Brazil and Colombia, constraints in the healthcare system and insufficient personal protective equipment were reported. Additionally, in Brazil, financial strain and working in deprived areas also impacted HCWs’ mental health.ConclusionImproving healthcare system preparedness, reducing inequities across facilities, and combating misinformation and violence are crucial for alleviating the mental burden on HCWs in future global crises.